The Effectiveness of Grammar Translation Method Towards Students’ Reading Comprehension at MA Darul Ulum Ngabar Mojokerto - Lus Firdaus Zakiya (Kirana Publisher (KNPub), 2026)
Reading comprehension is one of the language skills that need to be developed in students. Indeed, reading comprehension has become something that is fundamental and essential for students because the one of the students’ success is highly depends on their reading ability. If students’ reading comprehension is lacking, it is likely that students will fail academically, or at least have difficulty making progress. this research is to measure the effectiveness of the Grammar Translation Method toward students reading achievement at the tenth grade students. There are three types of experimental research, namely Pre-Experimental, True Experimental, Quasi-Experimental research. Researchers used a One-Group Pretest-Posttest research design. This design combines pretest and posttest by conducting a test on one group before being given treatment and after being given treatment. The pretest is given at the beginning before being treated and the posttest is given after the treatment is finished. The population is 74 students. The sample was class B, totaling 25 students. The researcher calculated the data by using T test in SPSS. Before applying the Translation Grammar Method, the average pre-test result score was 57,56 and there was an average post-test score of 85,76. The results of the T-Test above show a sig. (2-tailed) value of 0.00>0.05, which states that there is a difference after applying the Translation Grammar Method to improve the ability to read descriptive texts or in other words, H1 is accepted and H0 is rejected.